The Relationship Between Mothers' Knowledge Level and Stunting Prevention Efforts in Toddlers at Public Health Center X, West Jakarta - Trima Mirasa; Maria Susila Sumartiningsih (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2026)
Background: Stunting is one of the major public health issues affecting children and remains a serious concern, particularly in underdeveloped and developing countries. Stunting in toddlers has more severe consequences, including impaired cognitive development, reduced physical growth, functional disorders, and increased risk of mortality. Objective: This study aimed to determine the relationship between mothers’ knowledge levels and stunting prevention efforts among toddlers at Puskesmas X, West Jakarta. Methods: This study employed an analytic observational design with a cross-sectional approach. The sample consisted of 98 respondents selected from a population of 5,057 using quota sampling. Data analysis included univariate and bivariate analyses using the Chi-square test. Results: Univariate analysis showed that 84 respondents (85.7%) had a good level of knowledge regarding stunting prevention, while 14 respondents (14.3%) had a moderate level of knowledge. A total of 58 respondents (59.2%) demonstrated good stunting prevention efforts, whereas 40 respondents (40.8%) showed moderate prevention efforts. Bivariate analysis revealed a p-value of 0.059 (p > 0.05). Conclusion: The study concluded that there was no significant relationship between mothers’ knowledge levels and stunting prevention efforts among toddlers at Puskesmas X, West Jakarta. It is recommended that health promotion activities on stunting prevention be strengthened for families and the community during the critical period of toddler growth and development.